2021
DOI: 10.3390/su132011309
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Institutional Quality on FDI: Are There Promotional Effects in Economic Integration Regions?

Abstract: The purpose of this study is to examine the impact of institutional quality on foreign direct investment (FDI) using panel data of 117 countries around the world from the period of 2001 to 2018. To enhance the accuracy of the estimation results, this study includes various statistical tests to select the estimation method that best fits the sampling data used in this study. Furthermore, while the robust standard error is applied to correct the problem of heteroscedasticity, this study addresses the potential e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In the field of environmental research, numerous studies, like [ 11 ] and [ 30 ] used this indicator. [ 52 ] examined the relationship between institutional quality, economic growth, and foreign direct investment by using panel data to conduct their research. This study uses the methodology proposed [ 52 ]for the analysis of panel data, and as a result, the empirical baseline model equation can be stated as follows: …”
Section: Methodsmentioning
confidence: 99%
“…In the field of environmental research, numerous studies, like [ 11 ] and [ 30 ] used this indicator. [ 52 ] examined the relationship between institutional quality, economic growth, and foreign direct investment by using panel data to conduct their research. This study uses the methodology proposed [ 52 ]for the analysis of panel data, and as a result, the empirical baseline model equation can be stated as follows: …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the quality of institutions determines inward Foreign Direct Investment (FDI). In relation to this, Owusu-Nantwi (2019), Yakubu (2020) and Chen and Jiang (2021) indicate that better institutional quality contributes to attract more FDI. In a study based on a cross-country comparison of economic performance, Gwartney (2009) highlighted the importance of economic freedom on private investment.…”
Section: Literature Review 21 Theoretical Considerationmentioning
confidence: 96%
“…(2018) having analyzed data for 29 emerging countries show that improving institutional quality would attract more foreign investment and make competition with local firms fiercer. Chen and Jiang (2021) examined the effect of institutional quality in a panel of 117 countries by employing the panel GMM model for analysis. The findings of the study show that improvement in institutional quality positively impacts FDI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study involving 28 EU member states by Dobrowolska, Dorożyński and Kuna-Marszałek (2021) revealed a significant relationship between institutional quality and FDI inflows. Chen and Jiang (2021) found that in 42 G20 countries, institutional quality attracted FDI inflows by increasing trade openness, accelerating industrial structure optimization and encouraging technological innovation.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Some studies investigating the role of institutional quality variables on FDI inflows have been carried out in some economic blocs outside the ECOWAS with varying outcomes. Such studies include the work of Dobrowolska, Dorożyński and Kuna-Marszałek (2021) on 28 EU member states as well as a study by Chen and Jiang (2021) for 42 G20 countries. The study by Oshota and Wahab (2022) concentrated on the impact of institutional quality variables on trade flows in the ECOWAS countries.…”
Section: Introductionmentioning
confidence: 99%